Changing landscape of respiratory conduct and its stressful impact during covid-19 crisis - Sahar Mudassar, Mudassar Ali, Bilal Habib, Farukh Bashir, Shoaib Ahmed, Amna Mubeen, Umber Nisar, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The country was placed under a nationwide lockdown on April 1st, which was then extended twice more until May 9th. When the lockdown came to an end, it was gradually lifted. Following the initial wave, the nation has fought COVID-19 by implementing "smart lockdowns" and enforcing standard operating procedures (SOPs). Aims: To assess participants' respiratory etiquette, anxiety, and depression in the context of the COVID pandemic after the constraint of lockdown has been lifted. Methods: From May 2020 to February 2021, a total of 120 participants participated in this cross-sectional study. Data collection is done through the use of a proforma. Anxiety and depression were measured using the GAD-7 and PHQ-9 scales, which were used in conjunction with each other. It was disseminated by a deliberate snowball sampling procedure. Consent was obtained through the use of Google Forms. Results: Only 30 percent of the 120 participants wore a mask at all times. Anxiety and despair were experienced by 49 percent and 42 percent of those surveyed, respectively. Anxiety and depression were shown to be related with 35-50 year old females, HCPs, and family members who tested positive for COVID-19. Conclusions: Following the lockdown, participants' respiratory hygiene etiquette may have deteriorated, maybe due to their decreased anxiety about COVID-19 infection. Females, HCPs, and family members who tested positive for COVID-19 were shown to have higher levels of anxiety and sadness than other groups.